Hesperidin improves the follicular development in 3D culture of isolated preantral ovarian follicles of mice. Issue 5 (April 2019) - Shoorei, Hamed; Banimohammad, Majid; Kebria, Maziar M; Afshar, Mohammad; Taheri, Mohammad MH; Shokoohi, Majid; Farashah, Mohammad SG; Eftekharzadeh, Mina; Akhiani, Omid; Gaspar, Robert; Pazoki-Toroudi, Hamidreza
In vitro follicular culture systems provide optimal culture models for research about the physiology of the ovary and support the clinical practices to achieve competent mature oocytes for in vitro fertilization. In vitro maturation of preantral follicles makes it possible to study the effects of therapeutic agents on various conditions or disorders of the ovary. Nowadays, preventive bioflavonoids against cancer, hypercholesterolemia, fatty liver, or a variety of toxic agents are in focus. The aim of this study was to design and investigate the impacts of different concentrations of hesperidin, a glycoside flavonoid, on the in vitro preantral follicle growth and maturation in the three-dimensional (3D) culture system which was made with sodium alginate. Preantral follicles (n = 1363) were mechanically isolated from immature mice ovaries, then, after capsulating, they were randomly divided into four groups: the control group received no concentration of hesperidin, and three experimental groups were supplemented with 10, 22.5, and 50 µmol/L of hesperidin . All groups were cultured for 12 days. At the end of the culture period, the percentage of survival rate, antrum formation, obtained metaphase II oocytes, and the secretion of 17β-estradiol and progesterone were significantly higher in the group Hesp 50 (50 µmol/L hesperidin ). Moreover, the mean average of follicular diameter cultured in the group Hesp 50 was also increased and the mRNA expression levels of PCNA, FSH-R, and Bcl-2 genes were higher, while Bax mRNA expression was significantly reduced compared with the other groups. Follicles cultured in the presence of 50 µmol/L of hesperidin had a higher fertilization rate and embryo development. Adding hesperidin at the concentration of 50 µmol/L to the culture medium resulted in higher follicular growth and maturation and increased the rate of in vitro fertilization and embryo development. Impact statement: It has been stated that hesperidin has many pharmacological effects, such as anti-inflammatory and antioxidant effects, antimicrobial activity, and anti-carcinogenic activity; but hesperidin and its derivatives have been under investigation as anti-fertility factors for a very long time. However, our results show that hesperidin can improve mice follicular growth and maturation during in vitro 3D culture. Hesperidin as an antioxidant factor could enhance the mRNA expression levels of two important genes involved in folliculogenesis, PCNA, and FSH-R. Our results prove for the first time that hesperidin not only has deleterious effects on follicular development but can also increase rates of in vitro fertilization and embryo development.